Altered Behavior in Encephalitis: Insights From the Australian Childhood Encephalitis Study, 2013-2018 - Rebecca Burrell; Cheryl A. Jones; Cheryl A. Jones; Philip N. Britton; Philip N. Britton; The PAEDS Network; Russell C. Dale; Christopher C. Blyth; Julia E. Clark; Nigel Crawford; Helen Marshall; Elizabeth J. Elliott; et al. (Frontiers Media S.A., 2021)
Altered mental status is a major criterion for a diagnosis of encephalitis to be made with alteration in behavior, a key manifestation of altered mental status. We reviewed all evaluated cases identified by the Australian Childhood Encephalitis study between May 2013 and June 2018, to review the frequency and features of altered behavior (ALB). ALB was reported in >72% of cases of childhood encephalitis in all three major etiologic groups (infectious, immune-mediated, and unknown). The duration of ALB was >7 days in a minority, but significantly more frequent in immune-mediated compared with infectious encephalitis (27 and 10%, respectively, p < 0.01). ALB was most frequently characterized as irritability/agitation (47%), which predominated in children aged <1 year, and among the leading infectious causes in this age group (enterovirus, parechovirus, and bacterial meningoencephalitis). ALB in the form of disorientation/confusion (25%) was most prominent in those aged >1 year and most frequent in immune-mediated encephalitis. Hallucinations, paranoia, and aggression were all infrequent; suicidality/self-harm was not observed. ALB was reported in 20 of 21 cases of anti-N-methyl-d-aspartate receptor (anti-NMDAr), 19% for >7 days, and disorientation/confusion was the most frequent feature. Only one case was reported as presenting with "psychosis" and was diagnosed with anti-NMDAr encephalitis. Clinician-reported ALB is frequent but most often non-specific in childhood encephalitis. A longer duration of ALB is associated with an immune-mediated cause. More specific psychiatric symptoms (hallucinations, paranoia) are very infrequent. ALB is a hallmark of anti-NMDAr encephalitis, but psychosis is uncommon in contrast to the disorder in adults.